GAMBARAN DARAH IKAN NILA (Oreochromis niloticus) DENGAN PENAMBAHAN DOSIS PREBIOTIK YANG BERBEDA DALAM PAKAN - Riski Hartika; Mustahal Mustahal; Achmad Noerkhaerin Putra (JURNAL PERIKANAN DAN KELAUTAN, 2014)
Prebiotics which are non-digestible ingredients that benefit the host by stimulating growth and activity of health promoting bacteria. This research aimed to know blood parameters of tilapia with the addition of different dose of prebiotics in feed. Fish were feed four times daily in ad satiation. The feed used was commercially feed with 32 % carbohydrates, 7 % lipids and 30 % proteins. The prebiotic used was extracted from sweet potato so called sukuh variety. The experiment were done with three treatments and three replicates, namely 0% prebiotic, 1% prebiotic and 2% prebiotic. The result showed that application of prebiotic in feed can promote better tilapia blood parameters and immune system compared to control. The treatment with the addition of 1% prebiotic showed best result to improve leucocyte, lymphocytes and the phagocytic index among other treatments.Keyword: blood parameters, immune system, prebiotic, Tilapia